First year Physics labs in a 'suitcase': Closing the loop - Siddiqui, Salim; Loss, Robert; Lawson, Glen; Yeo, Shelley (University of Western Australia, 2006)
It is becoming a growing trend that a greater percentage of full time university students are getting engaged in paid employment to meet their living expenses. As a result many students find it difficult to fulfil the course requirements satisfactorily at the same time. A survey conducted by Curtin Applied Physics in October 2000 revealed that 58% of the full time students studying physics for their first time work either part time or full time and therefore may be disadvantaged when compared with their full time non-working colleagues. This issue was addressed by modularising the Physics 113/114/115 units providing flexible module assessment. Over the last four years we have found that the flexible module assessment has worked well and students are generally satisfied with the structure, but some of the students are still finding it difficult to budget their time to attend laboratories to complete the unit. The laboratory program is an essential part of these units and is thus heavily weighted and requires a considerable time input by the students. To address this issue a portable laboratory program in the form of 'take home kits' has been designed so that students can effectively perform their physics labs off campus. The details of the initial plan of this project were presented at the Teaching and Learning Forum 2005. In this presentation we report the student feedback and outcomes of this project.